2011
DOI: 10.1002/mc.20744
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine a mediates pathogenesis of aggressive cutaneous squamous cell carcinoma by augmenting epithelial‐mesenchymal transition: Role of TGFβ signaling pathway

Abstract: Organ transplant recipients (OTRs) develop multiple aggressive and metastatic non-melanoma skin cancers (NMSCs). Yet, the underlying mechanism remains elusive. Employing a variety of immune-compromised murine models, immunoblotting, immunohistochemical and immunofluorescence techniques, we show that human squamous xenograft tumors in nude mice grow faster and become significantly larger in size following treatment with the immunosuppressive drug, cyclosporine A (CsA). Re-injected tumor cells isolated from CsAt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…As observed earlier [16], we found that CsA treatment led to the development of larger tumors as compared to the vehicle-treated controls (Figure 1A). These tumors continued to grow beginning from day 6 to day 14.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As observed earlier [16], we found that CsA treatment led to the development of larger tumors as compared to the vehicle-treated controls (Figure 1A). These tumors continued to grow beginning from day 6 to day 14.…”
Section: Resultssupporting
confidence: 89%
“…CsA treatment significantly increased the levels of proliferation markers cyclin D1 and proliferating cell nuclear antigen (PCNA) as compared to vehicle-treated control group (Figure 2A and B) confirming our earlier observation [16, 19]. However, administration of inhibitors of p38 or Akt alone or in combination to CsA-treated animals significantly decreased the expression of these proteins (Figure 2A and B and Suppl.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…CNIs inhibit Langerhans cells, 53,54 dermal dendritic cells (DC) 55,56 , and T-cell signaling and proliferation, and cyclosporine directly promotes tumour development 5759 . Inhibition of calcineurin enhances carcinoma development in mouse models, and correlative evidence in human SCC implicates induction of ATF3 and bypass of senescence 59,60 . Tacrolimus is increasingly used for OTRs due to a favourable side effect profile as compared to cyclosporine in some settings.…”
Section: Clinical Studies Linking Immunosuppression With Skin Cancermentioning
confidence: 97%
“…Unlike other cancers where the incidence has stabilized or decreased, the rate of NMSC continues to rise, both within the general population and especially within high-risk groups, such as immunocompromised organ transplant recipients. The incidence of cutaneous squamous cell carcinoma (SCC) is 60–100-fold greater in organ transplant recipients than the general population, and frequently patients are diagnosed with multiple, aggressive SCCs [3, 4]. Thus, the identification of new therapeutic targets in NMSC has significant clinical implications.…”
Section: Introductionmentioning
confidence: 99%